PENGARUH PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN LINGKUNGAN KERJA FISIK SEBAGAI VARIABEL MODERASI PADA PT. CITRA RIAU SARANA KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Saputra Hendra; Pramadewi Arwinence; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of working experience and workingdiscipline on employee performance with the physique working environment as amoderating variable at PT.citra riau sarana logas tanah darat subdistrict kuantansingingi regency. Population in this study include permanent employees ofPT,citra riau sarana t0 81 people. Primary data was collected by using aquestionnaire as an instrument to prove the result of the study, to test thehypothesis in this study, using multiple regression using spss software version forwindows. Sampling using non probability sampling method with saturatedsampling technique. The results of the study show that: 1)there is a significantinfluence between work experience on the performance of employee of PT.citrariau sarana. 2) there is a significant influence between the influence of disciplineon the performance of employee of PT.citra riau sarana. 3) there is a significantinfluence between work experience on employee performance and the workenvironment as a moderating variable at PT.citra riau sarana. 4) there is asignificant influence of work discipline on employee performance with the workenvironment as a moderating variable at PT.citra riau sarana. Keywords : experience, discipline, environment, performance